Osteochondral Allograft Transplantation: A Technical Note - Amar S. Vadhera BS; Kevin C. Parvaresh MD; Hasani W. Swindell MD; Jonathan S. Lee BA; Adam B. Yanke MD, PhD; Nikhil N. Verma MD; Brian J. Cole MD; Jorge Chahla MD, PhD (Video Journal of Sports Medicine, 2024)
Background: Chondral injuries in the knee are commonly discovered during knee arthroscopy procedures. Due to the poor restoration potential and avascular nature of cartilage, large defects are commonly treated with such surgical procedures. Treatment utilizing an osteochondral allograft (OCA) transplant for symptomatic focal cartilage defects in the patellofemoral joint has demonstrated strong, lasting clinical and radiographic outcomes. Indications: Active and otherwise healthy patients are indicated for surgery when presenting with significant joint-line pain and a large focal chondral defect verified on advanced imaging after an extensive course of nonoperative management. Technique Description: Beginning with diagnostic arthroscopy to confirm the large defect of the medial femoral condyle, we proceeded with OCA transplantation. A small medial peripatellar arthrotomy is performed. The fat pad is removed for visualization and retractors are placed both medially and laterally to appropriately visualize the defect. The defect is then sized according to the appropriate sizing guide. The guide is then placed perpendicular to the defect, and a central guide pin is drilled. A scoring reamer is used to carefully cut the size of the defect followed by a central reamer to prepare the defect. Any debris is removed, and the incision is thoroughly irrigated. The defect is then carefully measured in all four quadrants to match the donor. Any underlying bone is impacted for a stable base. A drill is then used for appropriate marrow venting underneath the defect. The corresponding donor site is selected and reamed with continuous irrigation to prevent thermal necrosis. The plug is removed and carefully measured to match the recipient site. The plug is thoroughly irrigated with pulse lavage to remove marrow elements. The graft is carefully inserted with gentle manual pressure until it is seated perfectly flush with the surrounding cartilage. Results: Clinical research has demonstrated good-to-excellent long-term survivorship of OCA transplantation. Long-term return to sport rates for recreational and competitive athletes are upward of 75%. Discussion/Conclusion: As surgical techniques continue to develop, surgeons should consider utilizing OCA transplants to treat large chondral defects in the patellofemoral joint. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.